Recovery of rare-earth metals from aqueous solutions by bio/adsorption using non-conventional materials: a review with recent studies and promising approaches in column applications - Costa, Talles Barcelos da; Silva, Meuris Gurgel Carlos da; Vieira, Melissa Gurgel Adeodato (Journal of rare earths, 2020)
The recovery of rare-earth metals (REMs) is of great economic and environmental interest, because of their high market prices and various industrial applications. Recently, with the increasing demand for high-purity rare-earth compounds, the separation and purification of these elements have gained considerable attention. The bio/adsorption process has been considered an alternative to recover these elements, by its simplicity, low cost and efficiency for recovery of REMs at low concentrations. This review article presents the recent progress regarding REM bio/adsorption published literature in batch system by different non-conventional bio/adsorbents, as well as a critical analysis of the technological challenges to be faced and future prospects. For this purpose, the best application model (isotherm, kinetics), thermodynamic quantities and selection of eluents for desorption studies are also discussed. Additionally, in this review, the application of different bio/adsorbent materials were reviewed extensively in terms of the removal and recovery of REMs in continuous fixed-bed adsorption and regeneration cycles. Finally, future aspects in bio/adsorption research and prospects for commercial applications were discussed. Unconventional REMs-containing resources, including mining and oil refining, are sources containing significant amounts of REMs. The bio/adsorption is considered a promising alternative to conventional processes for removal and recovery of rare-earth ions from secondary sources as industrial wastewater. [Display omitted]